The Effect Of Body Weight Training Crunch And Leg Raises On The Body Weight Of Residents Of Rachita Garden 3 Housing - Suherman Jaya; Ahmad Adil; Ilham Kamaruddin; Muh. Adnan Hudain; Fahrizal Fahrizal (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to: (1) determine the effect of body weight training crunch on the body weight of Rachita Garden 3 residents, (2) determine the effect of body weight training leg raises on the body weight of Rachita Garden 3 residents, and (3) determine the difference in the effect of body weight training crunch and leg raises on the body weight of Rachita Garden 3 residents. This study is an experiment with a research design that uses a two-group pretest-posttest design. The population used is male residents of Rachita Garden 3 housing with sampling based on their body mass index of 12 people. The division of groups in this study was by ordinal pairing. Group I used bodyweight training crunch exercises while group II used bodyweight training leg raises exercises. The results of the study showed that: (1) there was a significant effect of body weight training crunch exercises on the weight of Rachita Garden 3 residents, with a t-value of 10.954 > t table 2.570 with a significance of 0.001, (2) there was a significant effect of body weight training leg raise exercises on the weight of Rachita Garden 3 residents, with a t-value of 6.892 > t table 2.570 with a significance of 0.001, and (3) there was a difference in the influence of the difference in numbers where bodyweight training crunch exercises had a greater effect than leg raises on the weight of Rachita Garden 3 residents, with an average weight loss of body weight training crunch 0.8 > body weight training leg raises 0.6 which had an average difference of 0.2. So it can be concluded that bodyweight training crunch is slightly superior in weight loss compared to bodyweight training leg raises.